The Influence of Group Counseling with Cognitive Behavior Therapy to Improve Students' Self-Control: The Influence of Group Counseling with Cognitive Behavior Therapy to Improve Students' Self-Control - Bin Zain, Mawardi (At-Taujih: Jurnal Bimbingan dan Konseling Islam, 2024)
The purpose of this study was to see how muchinfluence group counseling using the Cognitive Behavior Therapy  approach has in improving self-control of class XI IPS studentsat SMAN 2 Selong. This type of research is a quantitative experimental study using the one group pre-test post-test design type, namely by measuring the level of student self-control using a pre-test instrument which then obtaineda sample of 13 people, the 13 samples were then given treatment for 5 meetings, after that researcher measured again using the post-test instrument to seehow much increase in student self-control was produced after being given treatment. The results of this study indicate that there is a significant influence of group counseling using the Cognitive Behavior Therapy approach on improving self-control of class XI IPS students at SMAN 2 Selong. This can be seen in the results of the wilcoxon test data analysis, which obtained research results of 0.001 ≤ 0.05, meaning that there is a significant influence of groupcounseling using the Cognitive Behavior Therapy approach to improve students’ self-control.   Keywords: Self-control, CBT